2013
DOI: 10.1007/s12237-013-9633-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Feeding Behavior of Ribbed Mussels (Geukensia demissa) in Two Urban Sites (Long Island Sound, USA) with Different Seston Characteristics

Abstract: The Atlantic ribbed mussel, Geukensia demissa, is found in salt marshes along the North American Atlantic Coast. As a first step to study the possibility of future cultivation and harvest of ribbed mussels for nutrient removal from eutrophic urban environments, the feeding behavior of ribbed mussels in situ was studied from July to October 2011. Two locations approximately 80 km apart were used as study sites: Milford Harbor (Connecticut; 41°12′42.46″N, 73°3′7.75″W) and Hunts Point (Bronx, New York; 40°48′5.99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 41 publications
5
33
0
Order By: Relevance
“…The seston variables recorded during this study were within the range of Hunts Point seston reported previously (TPM from 6.59 to 19.41 mg L À1 ; POM from 1.53 to 3.45 mg L À1 ; PIM from 4.88 to 15.95 mg L À1 ; and ORG from 15.71 to 29.87%) (Galimany et al 2013a), and we believe the values reported here are representative of typical conditions at this location. Hunts Point has characteristics of shallow, tidally mixed, estuarine ecosystems where tides, wind, and shallow depth result in resuspension of the sediment from the bottom, reducing the Clearance rate CR L h À1 (mg inorganic matter from both faeces and pseudofaeces per unit of time (mg h À1 ))/(mg inorganic matter (PIM; mg L À1 ) in bay water) Filtration rate FR mg h À1 CR Â total particulate matter (TPM; mg L À1 ) in the bay water Total rejection rate TRR mg h À1 mg of inorganic and organic matter from pseudofaeces per unit of time (mg h À1 ) Organic ingestion rate OIR mg h À1 (CR Â Particulate organic matter (mg L À1 ) in the water) À (rejection rate of organic matter (mg h À1 )) Absorption rate AR mg h À1 OIR À (egestion rate of organic matter) Absorption efficiency AE fraction AR/OIR Selection efficiency SE fraction 1 À [(organic fraction within pseudofaeces)/(organic fraction within total particles available in bay water)] relative organic content of suspended particulate matter (Hawkins et al 1996b;Velasco and Navarro 2005;Galimany et al 2011).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The seston variables recorded during this study were within the range of Hunts Point seston reported previously (TPM from 6.59 to 19.41 mg L À1 ; POM from 1.53 to 3.45 mg L À1 ; PIM from 4.88 to 15.95 mg L À1 ; and ORG from 15.71 to 29.87%) (Galimany et al 2013a), and we believe the values reported here are representative of typical conditions at this location. Hunts Point has characteristics of shallow, tidally mixed, estuarine ecosystems where tides, wind, and shallow depth result in resuspension of the sediment from the bottom, reducing the Clearance rate CR L h À1 (mg inorganic matter from both faeces and pseudofaeces per unit of time (mg h À1 ))/(mg inorganic matter (PIM; mg L À1 ) in bay water) Filtration rate FR mg h À1 CR Â total particulate matter (TPM; mg L À1 ) in the bay water Total rejection rate TRR mg h À1 mg of inorganic and organic matter from pseudofaeces per unit of time (mg h À1 ) Organic ingestion rate OIR mg h À1 (CR Â Particulate organic matter (mg L À1 ) in the water) À (rejection rate of organic matter (mg h À1 )) Absorption rate AR mg h À1 OIR À (egestion rate of organic matter) Absorption efficiency AE fraction AR/OIR Selection efficiency SE fraction 1 À [(organic fraction within pseudofaeces)/(organic fraction within total particles available in bay water)] relative organic content of suspended particulate matter (Hawkins et al 1996b;Velasco and Navarro 2005;Galimany et al 2011).…”
Section: Discussionsupporting
confidence: 84%
“…The organic matter in the seston was very similar throughout the study and much lower than the inorganic matter. The organic content of the seston ( f ) was 22.73 AE 3.88, 17.28 AE 0.99 and 18.82 AE 3.22% for the 3 different days of experiments, within the same range as observations made during 2011-12 at the same site (22.58 AE 4.32%) but much lower than the range observed in Milford Harbor (43.38 AE 9.21%) (Galimany et al 2013a).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations